Letter from Svante Arrhenius to Georg Bredig, October 1911 - Arrhenius, Svante (1911)
Svante Arrhenius (1859-1927) writes to Georg Bredig (1868-1944) to tell him about his travels to the U.S.A for a lecture series. He mentions the death of Jacobus van't Hoff (1852-1911), who was the first Nobel Prize winner in Chemistry. Van’t Hoff is considered one of the founders of physical chemistry.
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Hoff, J. H. van 't (Jacobus Henricus), 1852-1911; Lectures and lecturing; Nobel Prize winners